Evaluation of the Spiritual Care Needs of Patients with Cancer in a Chemotherapy Unit in Turkey - Kırca, Kamile (Journal of religion and health, 2024)
This study was conducted to determine the spiritual care needs of cancer patients receiving chemotherapy. A cross-sectional descriptive design was used to analyze a total of 104 patients at a university hospital in Turkey. The data were collected using the Spiritual Care Needs Scale. The mean age of the patients participating in the study was 61.0 (10.2). It was determined that 31.7% of the patients stated that the concepts of spirituality and spiritual care are related to religion and worship. As a result, it was found that the patients receiving chemotherapy had high-spiritual care needs. The dimensions in which the spiritual needs of the patients were remarkably high were belief and spiritual practices, being in peace and security, the love and support of their relatives and being informed about health. The spiritual care need score of the patients increased significantly with marital status (p = 0.001), having children (p = 0.002), having a chronic disease (p = 0.04) and having an undergraduate/graduate level education (p = 0.01). Nurses should be aware of patient's spiritual needs, plan patient-specific spiritual care practices, conduct more studies on the effects of spiritual care on the patient and family and create guidelines for spiritual care practices in patients receiving chemotherapy in Turkey.